Chain extender effect of 3-(4-hydroxyphenyl)propionic acid/layered double hydroxide in PBS bionanocomposites. (September 2017) - Totaro, Grazia; Sisti, Laura; Celli, Annamaria; Askanian, Haroutioun; Hennous, Mohammed; Verney, Vincent; Leroux, Fabrice
Graphical abstract: Highlights: The composites developed improve the processability of PBS by increasing its molecular weight with a hybrid chain extender system. The hybrid chain extender system is an alternative to the use of toxic chain extender molecules released by the matrix with consequently environmental and health problems. HPPA, hosted by LDH, has a tunable chain extender effect toward the matrix. The mechanical and end-use properties of PBS have been improved. The composites developed are completely "green" and with low environmental impact. Abstract: 3-(4-Hydroxyphenyl)propionic acid (HPPA), a biobased hydroxy acid, has been used as organic modifier in layered double hydroxides (LDHs) based on ZnAl and MgAl cations. PBS bionanocomposites have been prepared via in situ polymerization (with both types of clays) and melt blending (just with ZnAl-HPPA) obtaining completely green materials, potentially fully biodegradable. The filler loading is included within the range 1–10 wt%. The materials have been studied in terms of morphological, thermal and viscoelastic properties, resulting to have high thermal stability and huge mechanical reinforcement thanks to an excellent filler/polymer interfacial interaction highlighted by rheology experiments. HPPA, hosted by LDH, has a great chain extender effect toward the matrix. In particular, the melt blended samples, even if WAXD analysis evidence the formation of intercalated structures, show a tunable chain extender effect proportional to the composition and no gel-like structure has been produced. Moreover, LDHs, besides being bio and food compatibles, decrease the gas and solvents permeability of matrix and are potentially antibacterial and antioxidant; therefore such hybrid system is multifunctional and could be exploited in a wide range of applications.